A Management Algorithm Based on Delayed Bleeding After Wide-Field Endoscopic Mucosal Resection of Large Colonic Lesions - Burgess, Nicholas G.; Williams, Stephen J.; Hourigan, Luke F.; Brown, Gregor J.; Zanati, Simon A.; Singh, Rajvinder; Tam, William; Butt, Joshua; Byth, Karen; Bourke, Michael J. (Clinical gastroenterology and hepatology, 2014)
Bleeding is the main complication of wide-field endoscopic mucosal resection (WF-EMR) for large colonic lesions. Few studies have examined bleeding outcomes after WF-EMR, and there are no evidence-based guidelines for management of bleeding in this group. We analyzed outcomes of patients with clinically significant post-EMR bleeding (CSPEB) and present a management algorithm based on our findings. In a prospective study, we collected data from WF-EMR of sessile colorectal polyps 20 mm or larger from 1039 patients who participated in the Australian Colonic Endoscopic resection multicenter study from July 2008 through May 2012. Data included patient and lesion characteristics and procedural, clinical, and histologic outcomes. Patients participated in a structured telephone interview 14 days after the procedure; independent predictors of a moderate or severe outcome by American Society of Gastrointestinal Endoscopists criteria, or any intervention for hemostasis, were identified. Sixty-two patients had CSPEB (6.0%); 34 were managed conservatively (55%) and 27 underwent colonoscopy (44%). One patient had primary embolization. Endoscopic therapy was applied in 21 cases; 14 had active bleeding. Two of the conservatively managed cases underwent colonoscopy for rebleeding after discharge. On multivariable analysis, moderate or severe bleeding events were associated with hemodynamic instability (odds ratio, 12.3; P = .046) and low level of hemoglobin at presentation (odds ratio, 0.50 per 1.0 g/dL; P = .005). Intervention for hemostasis was associated with hourly or more frequent hematochezia (odds ratio, 36.7; P = .001), American Society of Anesthesiologists grade 2 or higher (odds ratio, 20.1; P < .001), and transfusion (odds ratio, 18.7; P = .003). Based on a multicenter prospective study, CSPEB resolves spontaneously in 55% of patients. We developed a risk factor–based algorithm that might assist physicians in the management of bleeding. Patients responding to initial resuscitation can be observed, with a lower threshold for intervention in those with the identified risk factors.